Hallucinations, sleep fragmentation, and altered dream phenomena in Parkinson's disease - Pappert, Eric J.; Goetz, Christopher G.; Niederman, Francie G.; Raman, Rema; Leurgans, Sue (Movement disorders, 1999)
In a series of consecutively randomized outpatients who had Parkinson's disease (PD), we examined the association of three behaviors: sleep fragmentation, altered dream phenomena, and hallucinations/illusions. Using a log‐linear model methodology, we tested the independence of each behavior. Sixty‐two percent of the subjects had sleep fragmentation, 48% had altered dream phenomena, and 26% had hallucinations/illusions. Eighty‐two percent of the patients with hallucinations/illusions experienced some form of sleep disorder. The three phenomena were not independent. The interaction between sleep fragmentation and altered dream phenomena was strongly statistically significant. Likewise, a significant interaction existed between altered dream phenomena and hallucinations/illusions. No interaction occurred between sleep fragmentation and hallucinations/illusions. Sleep fragmentation, altered dream phenomena, and hallucinations/illusions in PD should be considered distinct but often overlapping behaviors. The close association between altered dream phenomena and hallucinations suggests that therapeutic interventions aimed at diminishing dream‐related activities may have a specific positive impact on hallucinatory behavior.